Inovasi Perancangan Motif Batik Kembang Kopi Menggunakan Teknologi Digital - Rini, Denik Ristya; Pahlevi, Andreas Syah; Sutrisno, Andika Agung; Silah, Sumardianshah Bin (MAVIS : Jurnal Desain Komunikasi Visual, 2025)
Innovation in Batik motif design using digital technology is driven by the rapid advancement of technology that must be adjusted to simplify the process of making Batik designs. The use of digital techniques in motif design not only facilitates motif duplication but also helps in determining the color palette for Batik patterns. In addition, Batik designs can be implemented into clothing mock-ups or other products. This study uses a creative creation method, where the process begins with an observational study of objects as a source of inspiration for Batik motifs. Furthermore, design development is carried out using CorelDraw software, followed by color simulation, and the final stage is the creation of a mock-up of the Batik motif design on the finished product. The results of the development show that the use of digital techniques significantly streamlines and accelerates the process of developing Batik motifs, offering greater efficiency and flexibility in design implementation.